Position of a forensic accountant in the Federation of Bosnia and Herzegovina finance sector (The Journal of Forensic Accounting Profession, 2024)
The paper aims to identify the possibility of positioning the profession of forensic accountant in the financial sector of the Federation of Bosnia and Herzegovina (hereinafter FBiH). To answer the question of how the profession of forensic accountant could be introduced into the financial sector, qualitative research was conducted using the method of interviews with respondents who have many years of experience in the financial sector of FBiH.(Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2023-0008, pod licencom CC BY-NC-ND 4.0)
Keywords: forensic accountant; finance sector; Federation of Bosnia and Herzegovina